Food and Malaysian climbers at high altitudes / Roslina Ahmad … [et al.] - Ahmad, Roslina; Mohd Zahari, Mohd Salehuddin; Othman, Zulhan; Zulkifly, Muhammad Izzat (2011)
Research curiosity in high altitude namely in the mountain range has attracted scientists over the globe to understand how the physiological and biochemical changes occurs to the human body during expeditions. These studies are very important in providing information to those who are actively involved in rough outdoor activities like mountain climbing and trekking. Physiological scientists have discovered evidences on the effects of high altitude environment to human respiratory, cardivascular and general health. These evidences in fact have extending the body of .knowledge in the concerned areas. Besides physiological aspects, another significant area,' which also a central focus among the researchers is nutritional aspect. Nutrition scientists such as Rose et al, (1988); Butterfield et al, (1992); Reynolds, (1998) and Reynolds et al, (1999) have contributed to altitudes literature. However, all of them are among the western researchers. There is no available data or attemp made by Malaysian researchers on nutritional or food at high altitudes despite of our success in conquering many mountains peaks including the Mount Everest. Based on experience of Fauzan Hj Hassan and Dr. Anuar Suum as a first (1997) and second (2004) batches of Malaysian Everest expedition team, besides other rudiments, foods are considered one of the most vital elements at high altitude. As reported during expeditions all Malaysian climbers were losing a lot body weight, diarrhoea due to food consumed not suited to their appetite. This occurence raises a critical question of what is the best food for our climbers or those from equators regions in high altitudes environment.